Character Strengths and Positive Outcomes - Cheng, Chiau Chui; Mohd. Hashim, Intan Hashimah (School of Social Sciences, USM, 2017)
Character strengths have been defined as positive traits associated with individual differences. It has been explored as part of the personality that contributes to well-being, happiness and flourishing. This paper provides a review of the VIA Classification of character strengths and the relationships between character strengths and positive outcomes. Previous research shows that different character strengths predict different outcomes. From the review, character strengths have been found to generally increase life satisfaction, flourishing and leadership. Character strengths also have significant relationships with coping with stress, mastering online education system and recovering from addiction behaviour. Most of the studies were conducted in Western countries across a variety of population. The review highlights the importance of studying character strengths, especially in less studied samples such as Malaysia.